Changing lives and changing minds: the experiences of adoptive parents from application to approval. (July 2014) - Dance, Cherilyn; Farmer, Elaine
The recruitment and preparation of adoptive parents is currently high on the UK Government's agenda and a number of far-reaching changes in policy, processes and guidance have been introduced in recent months. The fundamental aim of adoption from care remains to provide, hopefully, stable and loving families for children whose parents cannot care for them, but the experiences of adoptive parents in this process have recently moved from the wings to centre stage. This article introduces the reflections of a group of adoptive parents (n = 27) about their experience of becoming adopters. The impact of delays in the process and experiences of the preparation and assessment period are discussed. There is a particular focus on adopters' thoughts about the sorts of children they felt they could parent and how these changed in the course of their approval journey.